Semiconductor film CuBi2O4, modified Pt - Puzikova, Darya; Dergacheva, Margarita; Khussurova, Gulinur; Leontyeva, Xeniya (The 8th International Conference on Nanomaterials and Advanced Energy Storage Systems; Nazarbayev University; National Laboratory Astana; Institute of Batteries, 2020)
Various methods for modifying the surface of semiconductors with platinum nanoparticles are presented in the literature: electrochemical and photoelectrochemical deposition, electrophoretic deposition, photoreduction, chemical deposition, vacuum deposition, atomic layer deposition. At the same time, chemical deposition of Pt, which does not require expensive vacuum and electrochemical equipment, seems to be the least energy-intensive and labor-intensive method. This method consists in applying a solution of H2PtCl6 to the surface of a semiconductor film and subsequent thermal thermal decomposition of this compound to platinum metal at temperatures above 400°C. The chemical deposition method of platinum nanoparticles on the surface of semiconductor CuBi2O4 electrodes by dip-coating from an aqueous solution of 5 mmol/L H2PtCl6 followed by annealing at 450°C is shown. The platinum content in the modified CuBi2O4 film was determined by scanning electron microscopy. It was found that during dip-coating of platinum, the obtained Pt nanoparticles are globules 50–200 nm in size. The deposition of Pt on the surface of CuBi2O4 electrodes leads to an increase in the photocurrent density by 20% (0.3M NaOH solution). Modification of CuBi2O4 electrodes with Pt nanoparticles leads to a decrease in the degradation of the photocurrent from 25% to 3% after 300 s of photopolarization measurements. High values of the quantum efficiency of the photocurrent, reaching 70%, and photoelectrochemical stability make it possible to consider CuBi2O4 electrodes modified with Pt nanoparticles as a promising system for use in photoelectrochemical solar cells and photoelectrochemical decomposition of water.
Keywords: platinum nanoparticles; chemical deposition method; modified Pt; Research Subject Categories::TECHNOLOGY